Preferences and acceptance of Czech and Spanish consumers regarding beef with varying intramuscular fat content - Fořtová, Jana; Del Mar Campo, María; Valenta, Jaroslav; Needham, Tersia; Řehák, Dalibor; Lebedová, Nicole; Bartoň, Luděk; Klouček, Pavel; Bureš, Daniel (Meat science, 2022)
Understanding the factors affecting meat eating quality and consumer demand is essential for estimating future trends in meat consumption. The objective of the study was therefore to compare Czech and Spanish consumer attitudes and preferences in relation to beef intramuscular fat content. Three hundred and one consumers participated in the study; they completed a sociodemographic questionnaire and evaluated grilled beef samples of three varying intramuscular fat contents (low, medium, high). The low-fat meat had an average intramuscular fat content of 1.3%, medium had 3.1% and high-fat had 5.2%. Sensory assessment scores tended to show a positive linear relationship with beef intramuscular fat content. While Czech assessors only noted differences in tenderness and overall acceptance between the beef samples, Spanish assessors were able to detect significant differences in all the descriptors evaluated. Age and gender affected the assessment scores of beef with different intramuscular fat contents.
Keywords: Marbling; Attitudes; chování spotřebitelů; maso; průzkumy a dotazníky; Animals; Consumer Behavior; Taste; Consumer study; Cross-culture differences; zvířata; skot; chuť; Czech Republic; Surveys and Questionnaires; Meat; Cattle; Česká republika